Understanding geometry dependent part behavior of thin walled structures in powder bed fusion of polymers - Jaksch, Andreas; Cholewa, Simon; Drummer, Dietmar (Procedia CIRP, 2022)
To exploit the full potential of lightweight design of powder bed fusion of polymers (PBF- LB/P), it is necessary to identify the influence of nonstandard geometries and volume-surface ratios for thin wall structures, since research is still ongoing focused on typical process-component relationships using mainly standard dog-bone samples. For this purpose, different geometries with different volume-surface ratios are produced. To obtain a holistic understanding, it is necessary to describe the mechanical characteristics, geometry, and surface roughness, but also the energy input as a function of the specific components. In this study, the energy densities of the individual geometries is calculated using unique exposure strategy scan vectors. Within the scope of the performed work, the effect of the surface area to volume ratios on the mechanical performance of different geometries in PBF-LB is introduced. Furthermore, an influence on the surface roughness of the components in dependence of the geometry is observed. With these results, design guidelines are established for thin-walled structures in PBF-LB.
CRIS-Team Scopus Importer:2023-03-29
Keywords: design rules; thin walled components; volume-surface ratio